Exile from Eden, or, After the hole - Smith, Andrew (Andrew Anselmo), 1959- (Simon & Schuster BFYR, 2019)
It's been sixteen years since an army of horny, hungry, six-foot-tall praying mantises forced Arek's family underground and into the hole where he was born; it's the only home he's ever known. But now, post-end-of-the-world, the army of horny, hungry praying mantises might finally be dying out, and Arek's ready to leave the hole for good. All he has are mysterious letters from Breakfast, a naked, wild boy traveling the countryside with his silent companion, Olive. Together, Arek and his best friend Mel, who stowed away in his van, navigate their way through the ravaged remains of the outside world. This long-awaited sequel to the irreverent, groundbreaking Printz Honor Book Grasshopper Jungle is stunning, compelling, and even more hilarious and beautifully bizarre than its predecessor.